The Rising Triad of Cesarean Scar Pregnancy, Placenta Percreta, and Uterine Rupture: A Case Report and Comprehensive Review of the Literature - Nikolina Docheva; Emily D. Slutsky; Nicolette Borella; Renee Mason; James W. Van Hook; Sonyoung Seo-Patel (Case Reports in Obstetrics and Gynecology)
As the rate of cesarean sections continues to rapidly rise, knowledge of diagnosis and management of cesarean scar pregnancies (CSPs) is becoming increasingly more relevant. CSPs rest on the continuum of placental abnormalities which include morbidly adherent placenta (accreta, increta, and percreta). A CSP poses a clinical challenge which may have significant fetal and maternal morbidity. At this point, no clear management guidelines and recommendations exist. Herein we describe the case of a second trimester CSP with rapid diagnosis and management in a tertiary care center. The case underscores the need for well-coordinated mobilization of resources and a multidisciplinary approach. A review of the literature is performed and deficits in universal management principles are underscored.